Adult ADHD Medications and Their Cardiovascular Implications - A. Sinha; O. Lewis; R. Kumar; S. L. H. Yeruva; B. H. Curry (Case Reports in Cardiology)
Attention-deficit/hyperactivity disorder (ADHD) is a chronic neurobiological disorder exhibited by difficulty maintaining attention, as well as hyperactivity and impulsive behavior. Central nervous system (CNS) stimulants are the first line of treatment for ADHD. With the increase in number of adults on CNS stimulants, the question that arises is how well do we understand the long-term cardiovascular effects of these drugs. There has been increasing concern that adults with ADHD are at greater risk for developing adverse cardiovascular events such as sudden death, myocardial infarction, and stroke as compared to pediatric population. Cardiovascular response attributed to ADHD medication has mainly been observed in heart rate and blood pressure elevations, while less is known about the etiology of rare cardiovascular events like acute myocardial infarction (AMI), arrhythmia, and cardiomyopathy and its long-term sequelae. We present a unique case of AMI in an adult taking Adderall (mixed amphetamine salts) and briefly discuss the literature relevant to the cardiovascular safety of CNS stimulants for adult ADHD.